Sweated Labour: Female Needleworkers in Industrializing Canada - McIntosh, Robert (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1993)
Until well into this century, the garment trades were one of the largest employers in manufacturing in Canada. The decline of artisanal clothing trades over the middle of the 19th century led to a marked growth in outwork and deteriorating labour standards. As the garment trades became rife with sweating, a process conditioned by the structured inequalities of class and gender, they became a major source of wage labour for women. Only in this century were steps taken which limited, but by no means ended, sweated labour in the garment industry. The impact of protective legislation has been slight; much more credit in the struggle against sweating has to be given to the industrial garment unions.